Aircraft fatigue : design, operational and economic aspects - 409803 Mann, J. Y.; Mann, J. Y.; Milligan, I. S.; Symposium on Aircraft Fatigue-Design, Operational and Economic Aspects (1967 : Melbourne) (Rushcutters Bay, NSW : Pergamon Press, 1972)
19